Antibacterial activity improvement of dental glass-ceramic by incorporation of AgVO3 nanoparticles. Issue 11 (November 2022) - Baptista, Inês O.; Alves, M.F.R.P.; Ferreira, S.; Santos, C.; Vieira, S.I.; Fernandes, M.H.V.
Abstract: Objective: This study aimed to investigate the role of the incorporation of an antibacterial nanoceramic (AgVO3 ) on the properties of a restorative dental glass-ceramic. Method: A commercially available restorative glass-ceramic, commonly designated as porcelain (IPS d.SIGN) was functionalized with an antibacterial agent (nanostructured β-AgVO3 ), synthesized by a hydrothermal route. Both functionalized and pristine samples were processed according to the manufacturer's instructions. All samples were characterized by X-ray diffraction, Rietveld refinement, particle size distribution, Scanning Electron Microscopy, chemical solubility, and Inductively Coupled Plasma Spectroscopy. Their antibacterial potential (Mueller-Hinton test) was analyzed against gram-positive ( Staphylococcus aureus ) and gram-negative bacteria ( Escherichia coli ). Results: The commercial glass-ceramic showed leucite (KAlSi2 O6 ) as the only detectable crystalline phase, and, for both strains, no antibacterial activity could be detected in the Mueller-Hinton agar plates test. A monophasic, needle-shaped, and nanometric β-AgVO3 powder was successfully synthesized by a simple hydrothermal route. After thermal treatment, glass-ceramic samples containing different percentages of β-AgVO3 showed a second crystalline phase of microline [K0.95 (AlSi3 O8 )]. For modified samples, inhibition halos were easily visible on the Mueller-Hinton test, which ranged from 11.1 ± 0.5 mm to 16.6 ± 0.5 mm and 12.7 ± 0.3 mm to 15.5 ± 0.3 mm in the S. aureus and E.coli cultures, respectively, showing that the halos formed were dose-dependent. Also, increasing the percentage of β-AgVO3 promoted a significant increase in chemical solubility, from 72 µg/cm 2 (samples with 1 wt% of β-AgVO3 ) to 136 µg/cm 2 (samples with 2 wt% of β-AgVO3 ), which was associated with the silver and vanadium ions released from the glass matrix. Significance: Our in vitro results indicate that IPS d.SIGN, as most of the dental glass-ceramics, do not exhibit antibacterial activity per se. Nonetheless, in this concept test, we demonstrated that it is possible to modify dental veneering materials giving them antibacterial properties by adding at least 2 wt% of β-AgVO3, a nanomaterial easily synthesized by a simple route.